State-of-the-art treatment alternatives for base of skull meningiomas: complementing and controversial indications for neurosurgery, stereotactic and robotic based radiosurgery or modern fractionated radiation techniques - Combs, Stephanie (Radiation oncology, 2012)
For skull base meningiomas, several treatment paradigms are available: Observation with serial imaging, surgical resection, stereotactic radiosurgery, radiation therapy or some combination of both. The choice depends on several factors. In this review we evaluate different treatment options, the outcome of modern irradiation techniques as well as the clinical results available, and establish recommendations for the treatment of patients with skull-base meningiomas.